Propuesta metodológica para la evaluación del riesgo de los sistemas de agua potable en Poblaciones rurales de hasta 5000 habitantes - Ojeda Salvatierra, Rodrigo Guillermo (2017)
Risk assessment in drinking water systems is a key stage in a water safety plan and is achieved by identifying hazards or hazardous events together with risk assessment. The general objective of the study is to develop a method to evaluate the risk of drinking water systems in rural populations of up to 5000 habitants through a bibliographical research and technical interviews, which guarantee the consumption of vital liquid. In addition, it sets specific objectives such as identifying methods for assessing the risk of existing drinking water systems; Inquire about indicators used for risk assessment and finally design a methodological proposal for the assessment of the risk of drinking water systems in rural populations. A research methodology was proposed with a qualitative approach; the basic modality of the research was based on bibliographical - documentary research and field research. The type of research was exploratory using a descriptive method and techniques of data collection based on observation, interview and general bibliographic system were applied. It was possible to identify different methods for the evaluation of the risk of drinking water systems used to improve the consumption of vital fluid in rural populations where the methodological proposals are based on the contrast of the probability of occurrence of a hazard or dangerous event versus the impact that Can generate in the components or factors that have a direct and indirect impact on a drinking water system. For the present research project a methodological proposal is presented through a diagram the same one that evaluated the risks in the potable water system of the rural parish of Chacras of the city of Arenillas, identifying the dangerous events and later realizing the estimation of the risk using an adapted semi-quantitative matrix.